2017
DOI: 10.1093/nar/gkx1033
|View full text |Cite
|
Sign up to set email alerts
|

TADB 2.0: an updated database of bacterial type II toxin–antitoxin loci

Abstract: TADB2.0 (http://bioinfo-mml.sjtu.edu.cn/TADB2/) is an updated database that provides comprehensive information about bacterial type II toxin–antitoxin (TA) loci. Compared with the previous version, the database refined and the new data schema is employed. With the aid of text mining and manual curation, it recorded 6193 type II TA loci in 870 replicons of bacteria and archaea, including 105 experimentally validated TA loci. In addition, the newly developed tool TAfinder combines the homolog searches and the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
252
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(256 citation statements)
references
References 28 publications
2
252
0
2
Order By: Relevance
“…Comparative genomics of 190 genomes of S. mutans strains revealed that SMU.166, SMU.167, and SMU.168 genes are highly conserved and present in all strains and thus, belong to the core‐genome of S. mutans species. Bioinformatics analysis of SMU.166/167/168 locus using the search engines TADB 2.0 and RASTA‐Bacteria for identifying TA loci in prokaryotes, predicted a putative type II toxin of 148 aa residues in length (predicted MW 16.9 kDa) encoded by SMU.167 gene with two possible partners, SMU.166 and SMU.168. The SMU.166 gene encodes a putative hypothetical protein of 171 aa residues and a theoretical MW of 19.4 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative genomics of 190 genomes of S. mutans strains revealed that SMU.166, SMU.167, and SMU.168 genes are highly conserved and present in all strains and thus, belong to the core‐genome of S. mutans species. Bioinformatics analysis of SMU.166/167/168 locus using the search engines TADB 2.0 and RASTA‐Bacteria for identifying TA loci in prokaryotes, predicted a putative type II toxin of 148 aa residues in length (predicted MW 16.9 kDa) encoded by SMU.167 gene with two possible partners, SMU.166 and SMU.168. The SMU.166 gene encodes a putative hypothetical protein of 171 aa residues and a theoretical MW of 19.4 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…Homologs of the res-xre Pl locus are present in the genomes of many bacterial species and currently the TA database TADB 2.0 lists 115 of them (Xie et al, 2018). However, apart from the four highly conserved residues in the encoded toxins, alignment of selected RES toxin protein sequences shows that the proteins exhibit relatively low levels of sequence identity.…”
Section: Res-xre Loci From Several Bacterial Species Function As Bonamentioning
confidence: 99%
“…Type II TA modules are remarkably abundant in some prokaryotic genomes (Pandey and Gerdes, 2005;Jørgensen et al, 2009;Xie et al, 2018). For example, Mycobacterium tuberculosis strain H37Rv, a major human pathogen, encodes a stunning 88 putative TA modules (Ramage et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In types II, IV, V, and VI, the antitoxins are small proteins whereas in types I and III, the antitoxins are small regulatory RNAs (Lobato‐Marquez et al, ). The type II members are most abundant in bacteria and MazEF as a representative has been extensively studied (Coray, Wheeler, Heinemann, & Gardner, ; Lobato‐Marquez et al, ; Xie et al, ). The toxin MazF as an endoribonuclease cleaves single‐stranded RNA at the “ACA” recognition sequence whereas MazE is the cognate antitoxin for neutralization of MazF toxicity (Y. Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%